2012
DOI: 10.1590/s0066-782x2012005000087
|View full text |Cite
|
Sign up to set email alerts
|

Função endotelial, perfusão uterina e fluxo central em gestações complicadas por Pré-Eclampsia

Abstract: Background: The physiopathology of Preeclampsia (PE) is characterized by a deficiency in the process of placentation, systemic endothelial dysfunction and Central Nervous System (CNS) hyperflow. From a clinical point of view, it would be interesting to determine the occurrence of these phenomena before the onset of clinical manifestations of the disease, raising the possibility of new methods for predicting PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Existing reports of FMD in the third trimester of normotensive pregnancy show mixed results, however impaired FMD in preeclamptic pregnancies is well-described (29, 30). We did not see evidence of pregnancy-induced change in FMD, though FMD/SS decreased over time in both groups.…”
Section: Commentmentioning
confidence: 97%
“…Existing reports of FMD in the third trimester of normotensive pregnancy show mixed results, however impaired FMD in preeclamptic pregnancies is well-described (29, 30). We did not see evidence of pregnancy-induced change in FMD, though FMD/SS decreased over time in both groups.…”
Section: Commentmentioning
confidence: 97%
“…These included studies in women with risk factors for preeclampsia [64], studies that combined low and high-risk women [54, 49, 74], and studies that compared low-risk women to high-risk women who subsequently developed preeclampsia [50, 51]. One small study observed a non-significant trend towards lower FMD in women who later developed preeclampsia [75].…”
Section: Fmd and Preeclampsiamentioning
confidence: 99%
“…Based on data from a study developed at HC-UFMG ( 8 ) , a cut-off value of 6.5% was utilized for the FMD results, with any results below such value being considered as altered.…”
Section: Methodsmentioning
confidence: 99%
“…Contrary to poor placental perfusion, that is the most striking event in the physiopathology of early PE (clinical manifestations before 34 weeks of gestation) as compared with late PE (manifestations after 34 weeks), endothelial dysfunction is present in both PE forms ( 6 - 8 ) . Thus, the evaluation of the endothelium function would be clinically interesting to predict any form of PE.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation